2011
DOI: 10.1183/09031936.00144711
|View full text |Cite
|
Sign up to set email alerts
|

Non-CPAP therapies in obstructive sleep apnoea: mandibular advancement device therapy

Abstract: Mandibular advancement devices (MADs) represent the main non-continuous positive airway pressure (non-CPAP) therapy for patients with obstructive sleep apnoea (OSA). The aim of the European Respiratory Society Task Force was to review the evidence in favour of MAD therapy. Effects of tongue-retaining devices are not included in this report.Custom-made MADs reduce apnoea/hypopnoea index (AHI) and daytime sleepiness compared with placebo devices. CPAP more effectively diminishes AHI, while increasing data sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
136
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(148 citation statements)
references
References 60 publications
8
136
0
1
Order By: Relevance
“…However, CPAP reduced AHI more efficiently and gave a higher success rate in all these studies. [10][11][12][13][14][15][21][22][23] Overall, these PSG outcomes (especially hypoxia) are of crucial importance with regard to survival and morbidity in subjects with OSA, which emphasizes the relevance of optimal suppression of respiratory disturbances and argues against OA's treatment effect on OSA in terms of these respiratory parameters, 31,32 indicating that OAs can be given only for those who refuse CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…However, CPAP reduced AHI more efficiently and gave a higher success rate in all these studies. [10][11][12][13][14][15][21][22][23] Overall, these PSG outcomes (especially hypoxia) are of crucial importance with regard to survival and morbidity in subjects with OSA, which emphasizes the relevance of optimal suppression of respiratory disturbances and argues against OA's treatment effect on OSA in terms of these respiratory parameters, 31,32 indicating that OAs can be given only for those who refuse CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, clinical studies have shown equal efficacy between both modalities on ambulatory blood pressure, daytime sleepiness, and quality of life, among other things [1]. These results may also be explained by good clinical use of MAD, since particularly in mild OSA, the compliance with CPAP is frequently far from optimal [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…We used self‐assessments of adherence, which is a limitation in the present study. Compliance monitors were not widely available when the study was designed 30. A later study, comparing the results of objectively measured adherence with subjectively reported use, found only a 30‐minute longer sleeping time in the subjective reports 31…”
Section: Discussionmentioning
confidence: 99%